UJI KESUKAAN DAN KANDUNGAN GIZI TUNA MENTAI SEBAGAI ALTERNATIF MAIN COURSE UNTUK MENCEGAH STUNTING - Novi Dwi Utami; Nani Ratnaningsih; Badraningsih Lastariwati (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Stunting is a condition where a person's height is shorter than someone's age. Inadequate energy and nutrient intake is a very important factor in stunting problems. This study aims to develop mentai rice products, determine the people's acceptance of mentai tuna development products and examine the nutritional content contained in these food products. This type of research is research and development (RD) with 4D design (Define, Design, Develop, and Disseminate). The panelists used were 2 expert panelists and 30 trained panelists and used laboratory tests. The results of the validation of 2 expert panelists showed the number 3.88 in other words the mentai tuna product can pass the validation stage with very good values, the sensory test results of 30 trained panelists had an average of 3.85 or it could be interpreted that the mentai tuna product was highly accepted by consumers. The results of laboratory tests showed that the nutritional content of mentai tuna consisted of protein 11.75 grams, fat 6.38 grams, carbohydrates 37.43 grams, energy 254.06 kcal and iron 1.43 miligrams per 150 grams of product.